PERAN PASUKAN KONTINGEN GARUDA (KONGA) DALAM MISI PEMELIHARAAN PERDAMAIAN DUNIA DI REPUBLIK DEMOKRATIK KONGO TAHUN 2018-2020 - Rahman, Ridho; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research aims to analyze the role of the Garuda Contingent Force (Konga) in the world peacekeeping mission in the Democratic Republic of Congo in the 2018-2020 period. The research method used is qualitative analysis using secondary data from official reports, articles, and related literature. The results showed that the Konga Force played a significant role in maintaining stability and security in the Democratic Republic of Congo. They perform peacekeeping duties effectively through manning security posts, monitoring conflicts, and enforcing the law in the areas they secure. Furthemore, the troops also play a role in providing humanitarian assistance to the local population. They are involved in food aid distribution, medical services, infrastructure development, and protection of vulnerable groups such as children and women. This helps improve the well-being of Congolese communities and contributes positively to the achievement of sustainable development goals. The research also highlights the importance of the training and capacity building conducted by the Konga Forces. They provide military training and technical knowledge to Congolese military and police personnel, with the aim of improving their ability to maintain security and address future conflicts. Overall, this research shows that the Garuda Contingent (Konga) Troops have an important role to play in the world peacekeeping mission in the Democratic Republic of Congo. Their contributions in maintaining stability, providing humanitarian assistance, and building local capacity are important factors in creating sustainable peace in the country. Keywords: KONGA, Congo, Peace, Peacekeeping Force